Exploring the experiences of nurses in providing HIV self-management discharge information at a tertiary hospital in the Cape Metropole - Arison, Mellissa Lindsay (Stellenbosch : Stellenbosch University, 2025)
Thesis (MNur)--Stellenbosch University, 2025.